4IR integration of information technology best practice framework in operational technology - Musa Shilenge; Arnesh Telukdarie (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: Since inception in the 1970s, Operational Technology (OT) systems were designed to operate in isolation from Information Technology (IT) systems mainly due to differences in objectives relating to Confidentiality, Integrity, Security and Availability (CISA). Additional diverse components include computing speed, and failure severity in terms of safety, environmental, and financial impact. With the onset of Industry 4.0 and the need for integration the worlds of IT and OT must operate in unison. The focal point of this research is to evaluate if an Information Technology Service Management (ITSM) best practice framework can be integrated into the operational technology domain. Design/methodology/approach: A qualitative desk research methodology initiates data gathering on the two key domains. A comparative analysis is subsequently adopted for results analysis. Thereafter, an application case of ITSM inclusive of OT is proposed and reviewed. Findings: After comparative analysis and application case, the research concludes that an IT best practice framework i.e. the Information Technology Infrastructure Library (ITIL) can be integrated and adapted into the operational technology domain to facilitate management of OT in a service management style. Practical implications: The key benefit of this work is the inclusion of OT in global IT best practices in this Fourth Industrial Revolution (4IR) era. Originality/value: This paper contributes to ongoing research in IT-OT integration by providing a unique perspective on OT management in the Fourth Industrial Revolution (4IR). Other researchers can utilize the research outcomes to apply ITSM in the OT domain where 4IR technologies have been implemented.
Keywords: 650; 4IR; operational technology; information technology infrastructure library; configuration management